Maize-legume intercropping in central Malawi: Determinants of practice - Silberg, Timothy; Richardson, Robert; Hockett, M.; Snapp, Sieglinde S. (Informa UK Limited, 2017)
In Malawi, population growth has reduced opportunities for farmers to expand and cultivate new land. The country's primary farming population is comprised of smallholders, many who cultivate monocultures of maize (Zea mays). To reduce negative outcomes from this practice, intercropping maize with legumes has been promoted. The sustainable intensification (SI) practice was once widely used, but has declined in recent decades. Little is known about the determinants of intercropping or its role in agricultural development. The objective of this study was to examine the drivers of intercropping among smallholders. We used multiple logistic regression analysis to estimate the determinants of intercropping based on a survey of 324 households. Smallholders who sold legumes were more likely to intercrop, contrary to literature positing intercropping as a practice primarily intended to enhance food security. In addition, complementary SI practices such as fertilizer, manure and compost application were more likely to have occurred on intercropped fields relative to sole maize fields. Furthermore, smallholder farmers appeared to apply more fertilizer to their intercropped fields relative to their sole maize fields. The study highlights the value of including field-level characteristics and household socioeconomic survey data to understand farming practices as a means to inform agricultural policy.